Pengaruh Capital Adequacy Ratio, Non Performing Financing, dan Return On Asset terhadap Penyaluran Pembiayaan pada Perbankan Syariah yang terdaftar di Otoritas Jasa Keuangan tahun 2015-2020 - Wahyuni, Endah Sri (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA) on Financing Distribution in Islamic banking registered with the Financial Services Authority (OJK) for the 2015-2020 period, both partially and simultaneous. This type of research is quantitative research. The population in this research is sharia banking listed on the Financial Services Authority (OJK) with certain criteria. The sampling method uses purposive sampling technique. The data source in this research is secondary data published by sharia banking companies registered with the Financial Services Authority for the 2015-2020 period. This research uses data testing tools, namely the classical assumption test and multiple linear regression and is processed using the SPSS application. The results of this research show that CAR has a negative and significant effect on financing distribution with a t value of -4.033 < t table -2.015 and a sig value of 0.000 < 0.05. NPF has no effect and is not significant on financing distribution with a t value of 0.159 < t table 2.015 and a sig value of 0.875 > 0.05. ROA is influential and significant with a t value of 2.051 > t table 2.015 and a sig value of 0.046 < 0.05. Simultaneously, the CAR, NPF and ROA variables have a positive and significant effect on financing distribution with a Fcount value of 6.829 > Ftable 2.92 and a sig value of 0.001 < 0.05